2005
DOI: 10.3136/fstr.11.207
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Streptomyces coelicolor .ALPHA.-Galactosidase Gene in Escherichia coli and Characterization

Abstract: An a-galactosidase gene belonging to glycoside hydrolase family ,1 from Streptomyces coelicolor was cloned and expressed in E. coli. The purified enzyme showed a single protein band on SDS-PAGE with a molecular mass of 0. kDa. It was quite stable from pH /.* to +*.* after treatment at .*ῌ for 0* min, and was thermally stable up to /*ῌ. The enzyme acted on galacto-oligosaccharides, galactomanno-oligosaccharides and galactomannans as well as plant a-galactosidases. It consisted of an N-terminal catalytic domain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
1
1
Order By: Relevance
“…The addition of Na + and K + in the media enhanced the activity of α-galactosidase produced by L. reuteri MF14C strain in our study. However, the addition of Na + and K + did not show significant effect on α-galactosidase activity in previous mentioned reports [27][28][29][30][31]. But the addition of Na + and K + did significantly enhance the activity of β-galactosidase produced from B. longum CCRC 15708 [19].…”
Section: Induction Of α-Galactosidase By Different Metal Ionscontrasting
confidence: 70%
See 1 more Smart Citation
“…The addition of Na + and K + in the media enhanced the activity of α-galactosidase produced by L. reuteri MF14C strain in our study. However, the addition of Na + and K + did not show significant effect on α-galactosidase activity in previous mentioned reports [27][28][29][30][31]. But the addition of Na + and K + did significantly enhance the activity of β-galactosidase produced from B. longum CCRC 15708 [19].…”
Section: Induction Of α-Galactosidase By Different Metal Ionscontrasting
confidence: 70%
“…Similarly, Garro et al [28] showed that 10 mM of Mn 2+ did not lead to an increase in α-galactosidase activity in L. fermentum CRL 251. Fridjonsson et al [29], Kondoh et al [30], and Carrera-Silva et al [31] showed that 1 mM of Mn 2+ did not significantly affect α-galactosidase activity in Streptomyces coelicolor, Thermus brockianus ITI360, and L. fermentum CRL 722, respectively. The addition of Na + and K + in the media enhanced the activity of α-galactosidase produced by L. reuteri MF14C strain in our study.…”
Section: Induction Of α-Galactosidase By Different Metal Ionsmentioning
confidence: 98%